Botulism and cavernous sinus thrombosis induced by Acute rhinosinusitis: A case report - Ali Tavassoli; Mahmood Sadeghi; Parviz Amrimaleh (Babol University of Medical Sciences, 2018)
Background: Botulism is an acute and rapidly progressive descending paralytic disease caused by a neurotoxin of clostridium botulinum. Case presentation: A 28-year-old woman presented with severe generalized ascending symmetrical muscle paralysis. The patient was intubated and transferred to the medical intensive care unit with several symptoms including: severe headache, dysphagia, dyspnea, ptosis, diplopia, and dry mouth. Despite being alert, pupils were bilaterally midriatic and had absent corneal reflux. Pansinusitis was seen in the paranasal sinus scan. At first, the movement of eyelids, head and neck were restored. The movement of the upper limbs (15th day) and chest wall (20th day), abdomen (25th day) and the lower extremities (32nd day) were then gradually restored. On 41st day, the patient was completely disconnected from the ventilator. Conclusions: Botulism should be a diagnosis in any patient with an acute progressive symmetrical descending paralysis. Sinus mucosal injury (acute sinusitis) can be inoculated with spores of botulinum